Antibodies: The major participants in maternal–fetal interaction. Issue 1 (19th October 2018) - Yang, Xin; Zhang, Caiji; Chen, Guozhen; Sun, Chengming; Li, Jinming
Abstract: The aim of this study is to improve our understanding of the mechanisms involved in maternal–fetal immune tolerance. We searched the related literatures and overviewed the major antibodies associated with pregnancy and described in details their possible roles in mediating maternal–fetal interactions. Antibodies classified into different types based on their functional or structural characteristics were summarized, including immunoglobulin G, blocking antibody, nonprecipitating asymmetric antibody, antiphospholipid antibody, antitrophoblast antibody and antipaternal antibody. The presence and levels of various circulating antibodies in pregnancy may play a crucial role in the occurrence, development and termination of pregnancy.